2014
DOI: 10.1103/physreve.89.012136
|View full text |Cite
|
Sign up to set email alerts
|

Weak ergodicity breaking in an anomalous diffusion process of mixed origins

Abstract: The ergodicity breaking parameter is a measure for the heterogeneity among different trajectories of one ensemble. In this report this parameter is calculated for fractional Brownian motion with a random change of time scale, often called "subordination". We proceed to show that this quantity is the same as the known CTRW case.PACS numbers: 05.40.Fb,05.40.Fb "Weak ergodicity breaking" is a term which occurred in the spotlight a few years ago, see for instance [1][2][3][4][5][6] with respect to observables s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 32 publications
(51 reference statements)
9
87
1
Order By: Relevance
“…Continuous time random walk processes with scale free waiting time distribution have a finite value for EB even in the limit ∆/T = 0 [26], similar to HDPs [33][34][35][36], while for scaled Brownian motion the ergodicity breaking parameter approaches zero in this limit [45,46].…”
Section: Observablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous time random walk processes with scale free waiting time distribution have a finite value for EB even in the limit ∆/T = 0 [26], similar to HDPs [33][34][35][36], while for scaled Brownian motion the ergodicity breaking parameter approaches zero in this limit [45,46].…”
Section: Observablesmentioning
confidence: 99%
“…As examples we mention continuous time random walk processes with scale free distributions of waiting times [7,[25][26][27][28][29]31], correlated continuous time random walks [44], as well as diffusion processes with space [32][33][34][35][36] and time [32,38,45,46] dependent diffusion coefficients and their combinations [47]. We also mention ultraslow diffusion processes with a logarithmic form for x 2 (t) and linear lag time dependence (8) of the time averaged MSD [48] as well as the ultraweak ergodicity breaking of superdiffusive Lévy walks [49].…”
Section: Observablesmentioning
confidence: 99%
“…SBM is maybe the simplest way to construct a stochastic process that exhibits anomalous diffusion. It is defined as x SBM (t) = x(t α ), where x(t) is a Brownian motion [22,23]. Its autocorrelation function reads for τ > 0,…”
Section: (T)/t Of the Process X(t)mentioning
confidence: 99%
“…However, differently from Brownian motion, it is strongly nonstationary [30]. Furthermore, Y * (t) turns out to be the mean-field approximation of the CTRW, as it describes the motion of a cloud of random walkers performing CTRW motion in the limit of a large number of walkers [29]. Recent investigation has also shown that SBM exhibits rich aging properties, which strongly differentiates it from the standard BM [42].…”
Section: B Scaled Bmmentioning
confidence: 99%
“…(1), while still showing distinct features if we look at other properties, like the multipoint correlation functions [22][23][24][25]. Among the most commonly applied to data analysis, we find the continuous-time random walk (CTRW) [2,26] and the scaled Brownian motion (SBM) [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%